2001
DOI: 10.1890/1051-0761(2001)011[0111:easfiw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Social Factors Influencing Wildfires in the Upper Midwest, United States

Abstract: Although the vast majority of contemporary wildfires in the Upper Midwest of the United States have a human origin, there has been no comprehensive analysis of the roles played by abiotic, biotic, and human factors in determining the spatial patterns of their origins across the region. The Upper Midwest, a 2.8 × 105 km2 area in the northern, largely forested parts of the states of Minnesota, Wisconsin, and Michigan, contains regions of varied land cover, soil type, human settlement densities, and land manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
75
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(89 citation statements)
references
References 40 publications
10
75
2
2
Order By: Relevance
“…Railways reflect a transportation corridor in Yichun, and national fire records reveal that the majority of fire occurrences during this study period were accidental and negligent fires caused by human activities in and around railways, fire accidents by machinery, or lack of controlled burning activities near the tracks and railway infrastructure. Similar negative correlation between distance to railway and fire frequency was reported in the Upper Midwest states and Missouri and boreal forest in China [50][51][52]. On the contrary, Guo et al [53] reported a positive relationship between fire and distance to railway in subtropical forest in China and [3] reported both positive and negative relationships with spatial distribution in the study area.…”
Section: Discussionsupporting
confidence: 79%
“…Railways reflect a transportation corridor in Yichun, and national fire records reveal that the majority of fire occurrences during this study period were accidental and negligent fires caused by human activities in and around railways, fire accidents by machinery, or lack of controlled burning activities near the tracks and railway infrastructure. Similar negative correlation between distance to railway and fire frequency was reported in the Upper Midwest states and Missouri and boreal forest in China [50][51][52]. On the contrary, Guo et al [53] reported a positive relationship between fire and distance to railway in subtropical forest in China and [3] reported both positive and negative relationships with spatial distribution in the study area.…”
Section: Discussionsupporting
confidence: 79%
“…These differences also determined which parts of the landscape were treated, so one of the primary reasons that fuels treatments were most influential in the mid-and high-elevation regions, and not in the low-elevation region, was simply a function of where most of the treatments occurred. The low-elevation region had the largest proportion of chaparral and WUI, which is why the fire regime was characterised by shorter fire rotation with more frequent, smaller fires (to reflect higher humancaused ignition frequency, but more effective suppression in human-dominated areas) (Cardille et al 2001;Sturtevant et al 2004;Syphard et al 2008). Although the chaparral and oak fuel types in the low elevation region had relatively rapid fire spread rates, there were few treatments in those areas to reduce the spread of fire.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are consistent with those reported by Badia et al (2000), whose research showed that the spatial distribution of forest fire in Spain responds to behavior patterns, which in turn are linked to typology and functioning of the territory. Cardille et al (2001) analyzed the social and environmental factors that influence the occurrence of forest fire in Minnesota, Wisconsin and Michigan (USA). According to their researches, the variations in forest cover, soil type, density of human settlement and land management strategies can influence the spatial pattern of forest fire.…”
Section: Discussionmentioning
confidence: 99%